Sobre la edad de la secuencia metasedimentaria que encaja las mineralizaciones auríferas vetiformes en la región del taraira (vaupés) (1995)
The metasedimentary sequence hosting the lode gold mineralizations in the Taraira (Vaupés) region, has been correlated or compared with stratigraphic units o sequences from other countries with ages ranging from from 2.600 to 2.000 My. Recent works carried out by MINERALCO S.A., suggest the possibility that the age of this sequence be more recent than the previously considered age: Precambrian, less than 1.200 My.